Simplify: (3w - 1) / (2w^2 + w - 3) - (2 - w) / (w - 1) - (w) / (1 - w)

1 answer

The only work so far I know to do is,
=(3w - 1) / (w^2 + w - 6) - (2 - w) /(w - 1) - (w) / (w - 1)
= (3w - 1) / (w - 1) (2w + 3) -(w + 2) / (w - 1) - (w) / (w - 1)

I don't know what to do from here.
Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions